Studi Pendahuluan: Kepiting Air Tawar (Parathelphusa maindroni) di Kawasan Geopark Merangin Provinsi Jambi - Wulandari, Tia; Ihsan, Mahya; Suprayogi, Dawam (ORGANISMS: JOURNAL OF BIOSCIENCES, 2023)
Geopark Merangin is one of the World’s Natural Heritages (Geological Heritage Site) in Jambi Province which under the auspices of UNESCO. The area has the potential to be developed into an eco-geotourism area. To support this development, monitoring is needed for geological diversity, biodiversity, and cultural diversity. One potential study that can be explored is the existence of freshwater crabs. To date, the existence of freshwater crab species in the waters of Geopark Merangin has not been reported. This study aims to collect freshwater crabs that can be found in the Geopark Merangin area as a preliminary study of freshwater crab diversity in that area. The result indicates that one of the freshwater crab can be found is Parathelphusa maidroni. The presence of P. maidroni in Geopark Merangin area can serve as bioindicator of good water quality and open up potential for the discovery of other species. Futhermore, the discovery of P. maidroni in the aquatic region of Geopark Merangin can be considered as an initial step towards the identification of various freshwater crab species in that area.  AbstrakKawasan perairan Geopark Merangin Provinsi Jambi merupakan salah satu warisan alam dunia (Geological Heritage Site) dibawah naungan UNESCO. Kawasan tersebut berpotensi untuk dikembangakan menjadi kawasan Eco-geowisata. Untuk mendukung pengembangan tersebut, perlu dilakukan monitoring baik dari keanekaragaman geologi, keanekaragaman hayati maupun keanekaragaman budaya. Salah satu kajian yang dapat digali potensinya yaitu keberadaan kepiting air tawar. Sampai saat ini belum dilaporkan keberadaan jenis-jenis kepiting air tawar yang ada di perairan Geopark Merangin. Penelitian ini bertujuan untuk mengkaji jenis kepiting air tawar yang dapat ditemukan di kawasan Geopark Merangin sebagai studi pendahuluan terkait keragaman kepiting air tawar yang ada di kawasan tersebut. Hasil penelitian menunjukkan salah satu jenis kepiting air tawar yang dapat ditemukan yaitu Parathelphusa maidroni. Keberadaan P. maidroni di kawasan perairan Geopark Merangin dapat menjadi bioindikator perairan yang masih baik, dan membuka potensi ditemukan jenis kepiting air tawar lainnya. Selain itu dengan ditemukannya P. maidroni di kawasan perairan Geopark Merangin dapat dijadikan sebagai langkah awal untuk dilakukannya pendataan dan eksplorasi jenis-jenis kepiting air tawar di kawasan tersebut.